Cardiovascular responses to microinjections of endomorphin-2 into the nucleus of the solitary tract are attenuated in the spontaneously hypertensive rat. (April 2015) - Kawabe, Tetsuya; Ueyama, Takashi; Hano, Takuzo; Sapru, Hreday N.
Abstract Stimulation of µ1-opioid receptors (M1ORs) in the medial nucleus solitarius (mNTS) by endomorphin-2 (EM2) elicits decreases in mean arterial pressure (MAP), heart rate (HR) and greater splanchnic nerve activity (GSNA) in Wistar rats. We tested the hypothesis that EM2-induced responses in the mNTS may be attenuated in the spontaneously hypertensive rat (SHR). Experiments were carried out in urethane-anesthetized, artificially ventilated, adult male SHR and Wistar-Kyoto rats (WKY). Alterations in responses to chemical stimulation of the hypothalamic arcuate nucleus (ARCN) after bilateral blockade of M1ORs in the mNTS were also studied. In SHR, microinjections of EM2 into the mNTS elicited smaller decreases in MAP, HR and GSNA compared to those elicited in WKY; smaller cardiovascular responses in SHR can be explained by lower expression of M1OR mRNA in the NTS of SHR compared to WKY. Decreases in MAP and GSNA and increases in HR were elicited by microinjections of N-methyl-d-aspartic acid (NMDA) into the ARCN of WKY. Bilateral blockade of M1ORs in the mNTS attenuated the decreases in MAP and GSNA and exaggerated the increases in HR elicited by the ARCN stimulation in WKY but not in SHR. Tonic inhibitory activity of neuropeptide Y/gamma-aminobutyric acid (NPY/GABA) neurons in the ARCN is attenuated in SHR; this observation may explain increases in MAP, GSNA and HR elicited by microinjections of NMDA into the ARCN of SHR. These results demonstrate that attenuation of EM2-induced responses in the mNTS of SHR may contribute to the excitatory responses elicited by ARCN stimulation in SHR.